2013
DOI: 10.3892/ol.2013.1550
|View full text |Cite
|
Sign up to set email alerts
|

Toward an understanding of the pathophysiology of clear cell carcinoma of the ovary (Review)

Abstract: Endometriosis-associated ovarian cancers demonstrate substantial morphological and genetic diversity. The transcription factor, hepatocyte nuclear factor (HNF)-1β, may be one of several key genes involved in the identity of ovarian clear cell carcinoma (CCC). The present study reviews a considerably expanded set of HNF-1β-associated genes and proteins that determine the pathophysiology of CCC. The current literature was reviewed by searching MEDLINE/PubMed. Functional interpretations of gene expression profili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 87 publications
0
11
0
Order By: Relevance
“…This transcription factor plays a role in endometrial regeneration, differentiation, decidualization, glycogen synthesis, detoxification, cell cycle regulation, implantation, uterine receptivity and a successful pregnancy (7). Furthermore, HNF1B regulates a subset of progesterone target genes and may act as a modulator of female reproduction (7). The immunohistochemical study revealed that the positive HNF1B staining was a frequent finding in clear cell carcinoma.…”
Section: Overexpression Of Genes and Their Transcripts In Ovarian Clementioning
confidence: 98%
See 2 more Smart Citations
“…This transcription factor plays a role in endometrial regeneration, differentiation, decidualization, glycogen synthesis, detoxification, cell cycle regulation, implantation, uterine receptivity and a successful pregnancy (7). Furthermore, HNF1B regulates a subset of progesterone target genes and may act as a modulator of female reproduction (7). The immunohistochemical study revealed that the positive HNF1B staining was a frequent finding in clear cell carcinoma.…”
Section: Overexpression Of Genes and Their Transcripts In Ovarian Clementioning
confidence: 98%
“…HNF1B induces cell cycle arrest and stimulates an anti-apoptotic response to oxidative stress-induced DNA damage (9). Therefore, elucidating the detailed association between HNF1B upregulation and the acquisition of cell cycle regulation under conditions of oxidative stress may improve understanding of the mechanisms used to repair DNA damage (7). A previous study identified the role of the HNF1B-mediated signaling pathway in a fail-safe mechanism for the oxidative stress-induced DNA damage response (10).…”
Section: Overexpression Of Genes and Their Transcripts In Ovarian Clementioning
confidence: 99%
See 1 more Smart Citation
“…Ovarian clear cell carcinoma (OCC) is the second most common type of epithelial ovarian cancer (EOC), comprising 5-25% of all ovarian cancers, depending on ethnicity [1,2]. Patients are managed for the other EOC histotypes with cytoreductive surgery and chemotherapy [3,4]. However, the platinum-based chemotherapy that is applied to other histotypes, such as the more common high-grade serous ovarian carcinoma (HGSOC), is often ineffective for OCC [4,5], with recurrent and high-stage disease particularly resistant to this treatment [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Patients are managed for the other EOC histotypes with cytoreductive surgery and chemotherapy [3,4]. However, the platinum-based chemotherapy that is applied to other histotypes, such as the more common high-grade serous ovarian carcinoma (HGSOC), is often ineffective for OCC [4,5], with recurrent and high-stage disease particularly resistant to this treatment [6][7][8][9]. The paucity of treatment options is reflected in the poorer prognosis of OCC compared to other EOC histotypes [7,10].…”
Section: Introductionmentioning
confidence: 99%